Use of Unfair Means in Examination: An Investigative Study - Haleem, Bushra; Tufail, Shahla; Naseem, Afshan (Annals of Human and Social Sciences, 2025)
The use of unfair means in examinations is a detrimental practice that undermines students' moral values and academic integrity. This study aimed to investigate the unfair means that employed by students during examinations. Adopting a quantitative research design, data were collected through a structured questionnaire administered to a randomly selected sample of 700 students from six faculties at the University of the Punjab. The findings indicated the presence of unfair practices during examinations. Furthermore, significant differences were identified across four key factors (i.e. face paucity of space, cheating for fun & show-off, Ineffective time management skills or overload, not knowing the boundaries, different method of cheating) from the perspective of demographic variables (i.e. male & female and self-support & morning program). The study recommends that educational institutions should ensure that students are adequately informed about examination policies, rules, and regulations at the beginning of each academic session to eradicate the unfair means in examination.